All-solid waste alkali-activated cementing material and preparation method thereof
By adjusting the raw material ratio and process flow in all solid waste alkali-induced gelling materials, the problems of low recycling rate of solid waste such as construction waste and poor material toughness are solved, and high-performance all solid waste alkali-induced gelling materials are achieved. Preparation, expanding its application scope in architecture and other fields.
Patent Information
- Application Number
- CN202411431133.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-07
AI Technical Summary
At this stage, the recycling rate of solid waste such as construction waste is low, and the application of alkali-activated gelling materials is limited, especially their poor toughness, which limits its wide application in construction and other fields.
All solid waste alkali-excited gelling materials are used, which include fly ash, slag, calcium carbide slag, regenerated micro powder, alkali exciter, organic monomer, crosslinker and initiator, and adjust the ratio and process of raw materials. process to improve the strength and toughness of the material.
It has improved the utilization rate of solid waste resources such as construction waste, reduced the amount of alkali excitants, enhanced the compressive strength, flexural strength and toughness of the materials, and expanded the application range of all solid waste alkali excitation gelling materials.
Smart Images

Figure CN119390366A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization, and specifically relates to an all-solid waste alkali-activated gelling material and a preparation method thereof. Background Art
[0002] The application of all-solid waste alkali-activated cementitious materials can reduce the use of cement, thereby reducing carbon dioxide emissions. All-solid waste alkali-activated cementitious materials usually use industrial waste slag, waste, etc. as raw materials. Through scientific processes and technical treatments, these wastes are converted into high-performance cementitious materials, realizing the comprehensive utilization of resources and reducing the exploitation and consumption of natural resources. The research on all-solid waste alkali-activated cementitious materials can not only reduce dependence on cement, but also improve the performance of building materials, such as enhancing the strength, durability, and corrosion resistance of materials, thereby improving the quality and service life of buildings. Through the research and application of all-solid waste alkali-activated cementitious materials, we can promote the transformation and upgrading of the building materials industry, promote green and sustainable development, and promote the optimization and upgrading of the economic structure.
[0003] At present, the recycling rate of construction waste is low, the amount of alkali activator used in alkali-activated cementitious materials is large, and the toughness is poor, which greatly limits the application of alkali-activated cementitious materials. In the context of dual carbon, the study of high-performance all-solid waste alkali-activated cementitious materials is of great significance for achieving carbon emission reduction, comprehensive resource utilization, improving material performance and promoting industrial transformation and upgrading.
[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0005] The object of the present invention is to provide a full-solid waste alkali-activated cementitious material and a preparation method thereof, so as to help solve or improve the current problem of low recycling rate of solid waste such as construction waste or limited application of alkali-activated cementitious materials.
[0006] In order to achieve the above-mentioned purpose, the present invention provides the following technical scheme: an all-solid waste alkali-activated cementitious material, which comprises the following components in parts by weight: 60-140 parts of fly ash, 200-360 parts of slag, 5-45 parts of carbide slag, 45-180 parts of recycled micropowder, 30-70 parts of alkali activator, 45-225 parts of organic monomer and 120-260 parts of water; and also comprises a cross-linking agent and an initiator.
[0007] Preferably, the organic monomer is acrylamide, the crosslinking agent is N-(hydroxymethyl)acrylamide and / or N,N-methylenebisacrylamide, and the initiator is ammonium persulfate and / or potassium persulfate; in parts by weight, the amount of the crosslinking agent is 0.04-2 parts, and the amount of the initiator is 0.09-5 parts.
[0008] Preferably, the all-solid waste alkali-activated cementitious material includes the following components, in parts by weight: 68-101 parts of fly ash, 200-305 parts of slag, 18 parts of carbide slag, 45-180 parts of recycled micropowder, 45 parts of alkali activator, 90-225 parts of organic monomer, 0.1-1.08 parts of cross-linking agent, 1.8-4.5 parts of initiator and 225 parts of water.
[0009] Preferably, the regenerated micropowder is prepared by a method comprising the following steps: (1) placing construction waste into a crusher and crushing it to a particle size of 20-30 mm to obtain construction waste particles; (2) introducing a gas containing carbon dioxide into the construction waste particles obtained in step (1) to carbonize them to obtain carbonized particles; (3) grinding the carbonized particles obtained in step (2) to micron level to obtain the regenerated micropowder.
[0010] Preferably, in step (2), the carbonization temperature is 80-100° C., the carbonization pressure is 0.15-0.25 MPa, and the carbonization time is 0.5-1 h.
[0011] Preferably, 90% of the particle sizes of the regenerated micropowder are within the range of 0.1-25 μm; and 90% of the particle sizes of all components of the all-solid waste alkali-activated cementitious material are below 35.3 μm.
[0012] The present invention also provides a method for preparing the all-solid waste alkali-activated cementitious material as described above, which adopts the following technical scheme: the method for preparing the all-solid waste alkali-activated cementitious material as described above comprises the following steps: step S1, drying fly ash, slag and carbide slag respectively; step S2, weighing fly ash, slag, carbide slag, regenerated micropowder, organic monomer, cross-linking agent and initiator according to the formula amount, and adding them into a stirring device in sequence for stirring and mixing until they are evenly mixed; step S3, weighing water and alkali activator according to the formula amount, adding them into a stirrer, and stirring to obtain a uniformly mixed activator solution; step S4, putting the raw materials evenly mixed in step S2 into the activator solution obtained in step S3, first stirring at a first stirring rate for a first time, and then stirring at a second stirring rate for a second time, to obtain the all-solid waste alkali-activated cementitious material.
[0013] Preferably, in step S4, the first stirring rate is 30-60 r / min, and the first time is 2-5 min; the second stirring rate is 90-110 r / min, and the first time is 2-5 min.
[0014] Preferably, in step S1, the drying temperature is 50-80°C and the drying time is 2.5-3.5h; in step S2, the stirring rate is 55-65r / min and the stirring time is 2-5min; in step S3, the stirring rate is 55-65r / min and the stirring time is 1-3min.
[0015] Beneficial effects:
[0016] The all-solid waste alkali-activated cementitious material of the present invention can not only improve the utilization rate of solid waste resources such as construction waste, but also reduce carbon emissions in industrial production. It reduces the amount of alkali activator used while improving the strength and toughness of the material, thereby expanding the application scope of the all-solid waste alkali-activated cementitious material in the fields of transportation, construction, water conservancy and solid waste resource utilization.
[0017] The all-solid waste alkali-activated cementitious material of the present invention utilizes carbide slag to replace part of the alkali activator, thereby reducing the amount of alkali activator used, increasing the utilization rate of recycled micropowder from construction waste, and integrating the organic reaction into the inorganic reaction system, thereby making the internal structure of the cementitious material denser, thereby preparing a high-performance all-solid waste alkali-activated cementitious material with high compressive strength, flexural strength and toughness index.
[0018] The construction waste regeneration micro powder in the all-solid waste alkali-activated cementitious material of the present invention is mechanically crushed, then introduced with industrial tail gas to carbonize it, and then put into an oven; after drying, it is ground. The chemical components of construction waste are mainly CaO, SiO2 and Al2O3. After carbonization, part of the hydration products in the construction waste regeneration micro powder will gradually transform into CaCO3.
[0019] In the all-solid waste alkali-activated cementitious material of the present invention, fly ash and slag are used as sources of silicon and aluminum, and the main chemical components are silicon dioxide and aluminum oxide. The slag also contains alkaline oxides such as calcium oxide. The activity of aluminosilicate in the regenerated micropowder is improved under the action of the alkaline activator. The regenerated micropowder slurry itself is weakly alkaline, and combined with materials with potential volcanic ash activity such as slag and fly ash, it is beneficial to promote the occurrence of hydration reaction. The main component of carbide slag is calcium hydroxide, which can be used as an alkaline activator to provide alkalinity. The regenerated micropowder in the all-solid waste alkali-activated cementitious material of the present invention contains a large amount of CaCO3, SiO2, Al2O3 and a small amount of unhydrated cement. The addition of regenerated micropowder, on the one hand, the fine particles in the regenerated micropowder can fill the pores between the hydration products; on the other hand, the CaO, SiO2, Al2O3 and a small amount of unhydrated cement in the regenerated micropowder continue to participate in hydration to generate various gel products, providing strength for the sample. Acrylamide is initially soluble in water, which is an endothermic reaction and will lower the overall environmental temperature. However, with the action of initiators and cross-linking agents, acrylamide undergoes a polymerization reaction in the alkali-activated gelling material system, releasing a large amount of heat energy, which increases the overall environmental temperature and promotes the action of the alkali activator, accelerating the formation of the main hydration products of the alkali-activated gelling material, namely CSH, CAH, and CASH.
[0020] The main feature of the material prepared by the present invention is that it reduces the amount of alkali activator, improves the recycling rate of solid waste resources, and has better performance. The main raw materials are all industrial waste, and the organic material raw materials are industrial grade, which has low cost. The preparation process of the alkali-activated all-solid waste alkali-activated cementitious material prepared by the present invention is relatively simple, and it can be directly mixed with water and stirred evenly. On the one hand, the current alkali-activated cementitious materials have a large amount of alkali activators and poor toughness. On the other hand, the recycling rate of construction waste is low, which is not conducive to reducing CO2 emissions in the construction field.
[0021] In summary, the present invention not only reduces the amount of alkali activator used, but also improves the utilization rate of construction waste, improves the mechanical properties of alkali-activated cementitious materials by adjusting the ratio of raw materials, and also has good environmental protection and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0023] Figure 1 A schematic diagram of the structure of PAM (polyacrylamide, i.e., a polymer of acrylamide) in the all-solid waste alkali-activated gelling material of the present invention provided in one embodiment of the present invention;
[0024] Figure 2The scanning electron microscope image (left) and energy spectrum diagram (right) of the all-solid waste alkali-activated cementitious material of Example 3. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0026] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0027] The present invention aims to provide a full-solid waste alkali-activated cementitious material in view of the current problems of low recycling rate of solid waste such as construction waste or limited application of alkali-activated cementitious materials (for example, at least one of poor strength and poor toughness).
[0028] The all-solid waste alkali-activated cementitious material of the embodiment of the present invention includes the following components in parts by weight: 60-140 parts of fly ash (for example, 60 parts, 80 parts, 100 parts, 120 parts or 140 parts), 200-360 parts of slag (for example, 200 parts, 240 parts, 280 parts, 320 parts or 360 parts), 5-45 parts of calcium carbide slag (for example, 5 parts, 15 parts, 25 parts, 35 parts or 45 parts), 45-180 parts of recycled micro powder (for example, 5 parts, 15 parts, 25 parts, 35 parts or 45 parts), 200-360 parts of slag (for example, 200 parts, 240 parts, 280 parts, 320 parts or 360 parts), 50-45 parts of calcium carbide slag (for example, 5 parts, 15 parts, 25 parts, 35 parts or 45 parts), 200-360 parts of slag (for example, 200 parts, 240 parts, 280 parts, 320 parts or 360 ... For example, 45 parts, 60 parts, 90 parts, 120 parts, 150 parts or 180 parts), 30-70 parts (for example, 30 parts, 40 parts, 50 parts, 60 parts or 70 parts) of base activator, 45-225 parts (for example, 45 parts, 90 parts, 135 parts, 180 parts, 200 parts or 225 parts) of organic monomer and 120-260 parts (for example, 120 parts, 150 parts, 180 parts, 210 parts, 240 parts or 260 parts) of water; also includes a crosslinking agent and an initiator. Among them, fly ash and slag serve as sources of silicon and aluminum, and their main chemical components are silicon dioxide and aluminum oxide; carbide slag can provide alkalinity and calcium ions to increase the content of hydration products; since the solubility of calcium hydroxide in carbide slag is low, although it is very alkaline, the pH value of the solution it can provide is limited, which is not conducive to improving the reaction rate, and it can only partially replace the activator; if the amount of organic monomer used is too small, it cannot play a role in improving the mechanical properties; if the amount of organic monomer used is too much, it will hinder the inorganic material and reduce the strength.
[0029] The all-solid waste alkali-activated gelling material of the embodiment of the present invention has the main feature of reducing the amount of alkali activator (in the research of the prior art, the commonly used all-solid waste gelling materials cannot do without a large amount of alkali activators, and the amount of alkali activators is generally about 16%), while improving the recycling rate of solid waste resources, it has more excellent performance. The main raw materials are all industrial wastes, and the organic material raw materials are industrial grade with low cost. The preparation process of the alkali-activated gelling material of the present invention is relatively simple, and it can be directly mixed with water and stirred evenly. The all-solid waste alkali-activated gelling material of the present invention helps to solve at least one of the problems of large amount of alkali activators, low utilization rate of solid waste resources, low strength and poor toughness in the existing alkali-activated gelling materials. The all-solid waste alkali-activated gelling material of the present invention can not only improve the utilization rate of solid waste, but also reduce carbon emissions in industrial production, reduce the amount of alkali activators, improve the strength and toughness of the material, and expand the application scope of the all-solid waste alkali-activated gelling material.
[0030] The carbide slag in the all-solid waste alkali-activated cementitious material of the embodiment of the present invention can replace part of the alkali activator and reduce the amount of alkali activator used; the addition of organic monomers, cross-linking agents and initiators makes it possible to integrate the organic reaction into the inorganic reaction system, so that the inorganic and organic reactions promote each other to form a double network structure, making the internal structure of the cementitious material denser, and preparing a high-performance all-solid waste alkali-activated cementitious material with high compressive strength and toughness index.
[0031] In summary, the all-solid waste alkali-activated cementitious material of the embodiment of the present invention not only reduces the usage of alkali activator, but also improves the utilization rate of construction waste, improves the toughness of the alkali-activated cementitious material, improves the mechanical properties of the alkali-activated cementitious material, and also has good environmental protection and economic benefits.
[0032] In a preferred embodiment of the present invention, the organic monomer is acrylamide, the crosslinking agent is N-(hydroxymethyl)acrylamide and / or N,N-methylenebisacrylamide, and the initiator is ammonium persulfate and / or potassium persulfate; in parts by weight, the amount of the crosslinking agent is 0.04-2 parts (for example, 0.04 parts, 0.1 parts, 0.5 parts, 1 parts, 1.5 parts or 2 parts), and the amount of the initiator is 0.09-5 parts (for example, 0.09 parts, 0.2 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts or 5 parts). Among them, acrylamide is used as an organic monomer. Acrylamide is soluble in water in the initial stage. With the action of initiator and cross-linking agent, acrylamide undergoes polymerization reaction in the alkali-activated gelling material system (forming PAM with a three-dimensional network structure), releasing a large amount of heat energy (polymerization reaction is an exothermic reaction), raising the temperature of the overall environment, and also promoting the action of the alkali activator, accelerating the generation of the main hydration products CSH, CAH, and CASH of the alkali-activated gelling material, and increasing the total amount of hydration products (acrylamide, initiator and cross-linking agent can play a role in improving mechanical properties in the present invention). The amount of cross-linking agent and initiator is determined according to the organic monomer; if the amount of organic monomer is too large, it will not only increase the cost, but also cause the performance of the all-solid waste alkali-activated gelling material of the present invention to deteriorate.
[0033] In a preferred embodiment of the all-solid waste alkali-activated cementitious material of the present invention, the all-solid waste alkali-activated cementitious material comprises the following components in parts by weight: 68-101 parts of fly ash (for example, 68 parts, 75 parts, 85 parts, 95 parts or 101 parts), 200-305 parts of slag (for example, 210 parts, 230 parts, 260 parts, 280 parts or 305 parts), 18 parts of calcium carbide slag, 45-180 parts of recycled micropowder (for example, 45 parts, 60 parts, 90 parts, 120 parts, 150 parts or 180 parts), 45 parts of base activator, 90-225 parts of organic monomer (for example, 95 parts, 125 parts, 155 parts, 185 parts or 215 parts), 0.1-1.08 parts of crosslinking agent (for example, 0.16 parts, 0.36 parts, 0.56 parts, 0.7 parts, 0.9 parts or 1.08 parts), 1.8-4.5 parts of initiator (for example, 1.8 parts, 2.1 parts, 2.7 parts, 3.2 parts, 3.5 parts, 3.9 parts, 4.2 parts or 4.5 parts) and 225 parts of water.
[0034] In a preferred embodiment of the present invention, the regenerated micropowder is prepared by a method comprising the following steps:
[0035] (1) placing construction waste in a crusher and crushing the crushed waste into particles with a diameter of 20-30 mm (e.g., 20 mm, 22 mm, 24 mm, 26 mm, 28 mm or 30 mm) to obtain construction waste particles;
[0036] (2) placing the construction waste particles obtained in step (1) in a curing kettle, introducing carbon dioxide gas to carbonize them (dry carbonization, introducing CO2 into a sealed container containing the construction waste particles), and obtaining carbonized particles;
[0037] (3) Grinding the carbonized particles obtained in step (2) to micron level to obtain regenerated micropowder. The construction waste is first mechanically crushed, then carbon dioxide is introduced to carbonize it, and then placed in an oven; after drying, it is ground. The chemical components of construction waste are mainly CaO, SiO2 and Al2O3. After carbonization, part of the hydration products in the regenerated micropowder of construction waste will gradually transform into CaCO3.
[0038] The present invention helps to improve the utilization rate of construction waste recycled micro powder and reduce industrial tail gas emissions. After a series of pretreatments such as crushing, carbonization and grinding of construction waste, the recycled micro powder of construction waste is applied to alkali-activated cementitious materials. Among them, the recycled micro powder contains a large amount of CaCO3, SiO2, Al2O3 and a small amount of unhydrated cement. With the addition of recycled micro powder, on the one hand, the fine particles in the recycled micro powder can fill the pores between the hydration products; on the other hand, the CaO, SiO2, Al2O3 and a small amount of unhydrated cement in the recycled micro powder continue to participate in hydration to generate various gel products, providing strength for the sample. The present invention performs dry carbonization on construction waste particles. On the one hand, the construction waste has participated in the hydration process when it was first used as a building, and as a component of the all-solid waste alkali-activated cementitious material of the present invention, it needs to be hydrated for the second time. The large amount of water used will reduce the mechanical properties of the material, so dry carbonization is adopted.
[0039] In addition, the pore size of the PAM formed in the present invention is ≤30 μm, and the construction waste is reused after being crushed, carbonized, ground, etc. On the one hand, a large number of CaCO3 crystals generated in the system can provide nuclei for gel formation; on the other hand, nano-CaCO3 crystals can fill the small particle pores of polyacrylamide in the three-dimensional network structure, thereby improving the density of the structure of the all-solid waste gelling material and enhancing the mechanical properties of the material.
[0040] In a preferred embodiment of the present invention, in step (2), the carbonization temperature is 80°C to 100°C (e.g., 80°C, 85°C, 90°C, 95°C or 100°C), the carbonization pressure is 0.15-0.25MPa (e.g., 0.15MPa, 0.18MPa, 0.2MPa, 0.23MPa or 0.25MPa), the concentration of carbon dioxide is 95%-100% (e.g., 95%, 96%, 97%, 98%, 99% or 100%), and the carbonization time is 0.5-1h (e.g., 0.5h, 0.6h, 0.7h, 0.8h, 0.9h or 1h). The main technical conception of the preparation of the regenerated micropowder is: crush the construction waste and put it into a closed device, and then introduce CO2. The carbonization process is mainly characterized by the reaction of CO2 with Ca(OH)2, CSH gel, etc. to form a large amount of CaCO3 crystals; finally, the carbonized construction waste is put into a grinding tank and ground to micron level to obtain construction waste recycled micro powder. Among them, the temperature, time and pressure of carbonization will affect the carbonization degree of construction waste particles and the content of carbonization products.
[0041] Preferably, the carbonization pressure is 0.25 MPa, the carbonization temperature is 100° C., and the carbonization time is 1 h.
[0042] In a preferred embodiment of the present invention, 90% of the particle sizes of the recycled micropowder in the all-solid waste alkali-activated cementitious material are within the range of 0.1-25 μm, and 90% of the particle sizes of all components of the all-solid waste alkali-activated cementitious material are below 35.3 μm.
[0043] In a preferred embodiment of the present invention, the all-solid waste alkali-activated cementitious material includes the following components, measured in parts by weight: 202 parts of slag, 68 parts of fly ash, 18 parts of carbide slag, 180 parts of regenerated micropowder, 135 parts of organic monomer, 0.15 parts of N,N-methylenebisacrylamide, 2.7 parts of ammonium persulfate, 45 parts of sodium silicate and 225 parts of water.
[0044] The present invention also proposes a method for preparing the all-solid waste alkali-activated cementitious material as described above. The method for preparing the all-solid waste alkali-activated cementitious material implemented by the present invention comprises the following steps: step S1, drying fly ash, slag and carbide slag respectively; step S2, weighing fly ash, slag, carbide slag, recycled micropowder, organic monomer, crosslinking agent and initiator according to the formula amount, and adding them into a stirring device in sequence for stirring and mixing until they are evenly mixed; step S3, weighing water and alkali activator according to the formula amount, adding them into a stirrer, and stirring to obtain a uniformly mixed activator solution; step S4, putting the evenly mixed raw materials in step S2 into the activator solution obtained in step S3, first stirring at a first stirring rate for a first time, and then stirring at a second stirring rate for a second time, to obtain the all-solid waste alkali-activated cementitious material. Among them, the first stirring rate, the first time, the second stirring speed and the second time are selected for the purpose of being able to dissolve and mix to form a uniform slurry, so as to help better ensure the authenticity and scientificity of the material's flexural strength, compressive strength and other properties. Specifically, you can refer to the national standard GB / T 17671-2021 "Test method for strength of cement mortar" and select according to actual conditions.
[0045] In a preferred embodiment of the method for preparing all-solid waste alkali-activated cementitious material according to the embodiment of the present invention, the first stirring rate is 30-60r / min (for example, 30r / min, 40r / min, 50r / min or 60r / min), and the first time is 2-5min (for example, 2min, 3min, 4min or 5min); the second stirring rate is 90-110r / min (for example, 90r / min, 100r / min or 110r / min), and the first time is 2-5min (for example, 2min, 3min, 4min or 5min).
[0046] In a preferred embodiment of the method for preparing an all-solid waste alkali-activated cementitious material according to an embodiment of the present invention, in step S1, the drying temperature is 50-80°C (for example, 50°C, 60°C, 70°C or 80°C), and the drying time is 2.5-3.5h (for example, 2.5h, 3h or 3.5h); in step S2, the stirring rate is 55-65r / min (for example, 55r / min, 60r / min or 65r / min), and the stirring time is 2-5min (for example, 2min, 3min, 4min or 5min); in step S3, the stirring rate is 55-65r / min (for example, 55r / min, 60r / min or 65r / min), and the stirring time is 1-3min (for example, 1min, 2min or 3min).
[0047] The all-solid waste alkali-activated gelling material and the preparation method thereof of the present invention are described in detail below through specific embodiments.
[0048] In the following examples: fly ash was purchased from Henan Yuanheng Environmental Protection Engineering Co., Ltd.; slag was purchased from Luoyang Yellow River Tongli Cement Co., Ltd.; construction waste was waste from construction sites around the school, and carbide slag was produced by Anyang Xinze Metallurgical Refractory Co., Ltd.; organic monomers, cross-linking agents, initiators, sodium silicate (solid particles) in the alkali activator, etc. were all commercially available industrial products, among which the modulus of sodium silicate was 1.2; anionic polyacrylamide was purchased from Guangzhou Yongsheng Chemical Company with a molecular weight of 18 million; acrylic acid and sodium acrylate were both commercially available analytical grade.
[0049] Tables 1 and 2 show the chemical composition and particle size of the inorganic materials used in the following examples.
[0050] Table 1 Chemical composition and content of raw materials (%)
[0051]
[0052] Table 2 Particle size of raw materials
[0053]
[0054] Example 1
[0055] The all-solid waste alkali-activated cementitious material of the embodiment of the present invention includes the following components, measured in parts by weight: 304 parts of slag, 101 parts of fly ash, 45 parts of regenerated micropowder, 18 parts of carbide slag, 135 parts of organic monomer (acrylamide), 0.15 parts of N,N-methylenebisacrylamide, 2.7 parts of ammonium persulfate, 45 parts of sodium silicate and 225 parts of water.
[0056] The regenerated micropowder is prepared by a method comprising the following steps:
[0057] (1) Putting construction waste into a crusher and crushing it for 30 minutes until the particle size is 20 mm to 35 mm, thereby obtaining construction waste particles;
[0058] (2) placing the construction waste particles obtained by the treatment in step (1) in a closed curing kettle and introducing CO2 to carbonize them (dry carbonization without water); wherein the carbonization temperature is set to 100° C., the pressure is set to 0.25 MPa, the carbonization time is 1 h, and the CO2 concentration is 95%;
[0059] (3) The carbonized construction waste particles are placed in a ball mill and ground to micron level to obtain recycled micro powder.
[0060] The method for preparing the all-solid waste alkali-activated gelling material according to the embodiment of the present invention comprises the following steps:
[0061] Step S1, add 304 parts of slag, 101 parts of fly ash, 45 parts of regenerated micropowder, 18 parts of carbide slag, 135 parts of organic monomer (acrylamide), 0.15 parts of N,N-methylenebisacrylamide and 2.7 parts of ammonium persulfate into a mixer and stir at a stirring rate of 60 r / min for 1 minute.
[0062] Step S2, weigh 45 parts of sodium silicate and 225 parts of water, add them into a stirrer, and stir at a stirring rate of 60 r / min for 2 minutes to obtain an activator solution.
[0063] Step S3, adding the uniformly mixed raw materials obtained in step S1 to the activator solution in step S2, stirring at a stirring rate of 60 r / min for 2 min, and then stirring at a stirring rate of 120 r / min for 2 min, to obtain the all-solid waste alkali-activated gelling material of this embodiment.
[0064] After the final setting of the sample, demould it and wrap it tightly with plastic wrap to test the subsequent performance.
[0065] Example 2
[0066] Step S1, add 270 parts of slag, 90 parts of fly ash, 18 parts of carbide slag, 90 parts of regenerated micropowder (the same as in Example 1), 135 parts of organic monomer (acrylamide), 0.15 parts of N,N-methylenebisacrylamide and 2.7 parts of ammonium persulfate into a mixer and stir at a stirring rate of 60 r / min for 1 min.
[0067] Step S2, weigh 45 parts of sodium silicate and 225 parts of water, add them into a stirrer, and stir at a stirring rate of 60 r / min for 2 minutes to obtain an activator solution.
[0068] Step S3, adding the uniformly mixed raw materials obtained in step S1 to the activator solution in step S2, stirring at a stirring rate of 60 r / min for 2 min, and then stirring at a stirring rate of 120 r / min for 2 min, to obtain the all-solid waste alkali-activated gelling material of this embodiment.
[0069] Example 3
[0070] Step S1, weigh 202 parts of slag, 68 parts of fly ash, 18 parts of carbide slag, 180 parts of regenerated micropowder (the same as in Example 1), 135 parts of organic monomer (acrylamide), 0.15 parts of N,N-methylenebisacrylamide and 2.7 parts of ammonium persulfate, add them into a mixer and stir at a stirring rate of 60 r / min for 1 min.
[0071] Step S2, weigh 45 parts of sodium silicate and 225 parts of water, add them into a stirrer, and stir at a stirring rate of 60 r / min for 2 minutes to obtain an activator solution.
[0072] Step S3, adding the uniformly mixed raw materials obtained in step S1 to the activator solution in step S2, stirring at a stirring rate of 60 r / min for 2 min, and then stirring at a stirring rate of 120 r / min for 2 min, to obtain the all-solid waste alkali-activated gelling material of this embodiment.
[0073] Example 4
[0074] Step S1, weigh 202 parts of slag, 68 parts of fly ash, 18 parts of carbide slag, 180 parts of regenerated micropowder (the same as in Example 1), 90 parts of organic monomer (acrylamide), 0.1 parts of N,N-methylenebisacrylamide and 1.8 parts of ammonium persulfate, add them into a mixer and stir at a stirring rate of 60 r / min for 1 min.
[0075] Step S2, weigh 45 parts of sodium silicate and 225 parts of water, add them into a stirrer, and stir at a stirring rate of 60 r / min for 2 minutes to obtain an activator solution.
[0076] Step S3, adding the uniformly mixed raw materials obtained in step S1 to the activator solution in step S2, stirring at a stirring rate of 60 r / min for 2 min, and then stirring at a stirring rate of 120 r / min for 2 min, to obtain the all-solid waste alkali-activated gelling material of this embodiment.
[0077] Example 5
[0078] Step S1, weigh 202 parts of slag, 68 parts of fly ash, 18 parts of carbide slag, 180 parts of regenerated micropowder (the same as in Example 1), 135 parts of organic monomer (acrylamide), 1.08 parts of N,N-methylenebisacrylamide and 2.7 parts of ammonium persulfate, add them into a mixer and stir at a stirring rate of 60 r / min for 1 min.
[0079] Step S2, weigh 45 parts of sodium silicate and 225 parts of water, add them into a stirrer, and stir at a stirring rate of 60 r / min for 2 minutes to obtain an activator solution.
[0080] Step S3, adding the uniformly mixed raw materials obtained in step S1 to the activator solution in step S2, stirring at a stirring rate of 60 r / min for 2 min, and then stirring at a stirring rate of 120 r / min for 2 min, to obtain the all-solid waste alkali-activated gelling material of this embodiment.
[0081] Example 6
[0082] Step S1, weigh 202 parts of slag, 68 parts of fly ash, 18 parts of carbide slag, 180 parts of regenerated micropowder (the same as in Example 1), 225 parts of organic monomer (acrylamide), 0.225 parts of N,N-methylenebisacrylamide and 4.5 parts of ammonium persulfate, add them into a mixer and stir at a stirring rate of 60 r / min for 1 min.
[0083] Step S2, weigh 45 parts of sodium silicate and 225 parts of water, add them into a stirrer, and stir at a stirring rate of 60 r / min for 2 minutes to obtain an activator solution.
[0084] Step S3, adding the uniformly mixed raw materials obtained in step S1 to the activator solution in step S2, stirring at a stirring rate of 60 r / min for 2 min, and then stirring at a stirring rate of 120 r / min for 2 min, to obtain the all-solid waste alkali-activated gelling material of this embodiment.
[0085] Example 7
[0086] Step S1, weigh 202 parts of slag, 68 parts of fly ash, 9 parts of carbide slag, 180 parts of regenerated micropowder (the same as in Example 1), 135 parts of organic monomer (acrylamide), 0.15 parts of N,N-methylenebisacrylamide and 2.7 parts of ammonium persulfate, add them into a mixer and stir at a stirring rate of 60 r / min for 1 min.
[0087] Step S2, weigh 54 parts of sodium silicate and 225 parts of water, add them into a stirrer, and stir at a stirring rate of 60 r / min for 2 minutes to obtain an activator solution.
[0088] Step S3, adding the uniformly mixed raw materials obtained in step S1 to the activator solution in step S2, stirring at a stirring rate of 60 r / min for 2 min, and then stirring at a stirring rate of 120 r / min for 2 min, to obtain the all-solid waste alkali-activated gelling material of this embodiment.
[0089] Comparative Example 1
[0090] The difference between this comparative example and Example 3 is that: acrylamide organic monomer, initiator and cross-linking agent are omitted (that is, the all-solid waste alkali-activated cementitious material of this comparative example includes: 202 parts of slag, 68 parts of fly ash, 18 parts of carbide slag, 180 parts of regenerated micropowder, 45 parts of sodium silicate, 0 parts of organic monomer, 0 parts of N,N-methylenebisacrylamide and 0 parts of ammonium persulfate); the rest are consistent with Example 3.
[0091] Comparative Example 2
[0092] The difference between this comparative example and Example 3 is that the acrylamide organic monomer, initiator and cross-linking agent are replaced by polyacrylamide (that is, the alkali-activated gelling material of this comparative example includes the following components in parts by weight: 202 parts of slag, 68 parts of fly ash, 18 parts of carbide slag, 180 parts of regenerated micropowder, 45 parts of sodium silicate, and 0.45 parts of polyacrylamide); the rest are consistent with Example 3.
[0093] Among them, the amount of polyacrylamide added in this comparative example is the optimal amount of addition measured in the experiment (polyacrylamide in this comparative example mainly plays the role of thickening, improving slurry stability, and preventing water from easily seeping; if the amount of polyacrylamide is too large, the viscosity will increase, making it difficult to mix the raw materials evenly and impossible to experiment).
[0094] Comparative Example 3
[0095] The difference between this comparative example and Example 3 is that the amount of regenerated micropowder is replaced with 200 parts (that is, the alkali-activated cementitious material of this comparative example includes the following components in parts by weight: 189 parts of slag, 63 parts of fly ash, 18 parts of carbide slag, 200 parts of regenerated micropowder, 45 parts of sodium silicate, 135 parts of organic monomer, 0.15 parts of N,N-methylenebisacrylamide and 2.7 parts of ammonium persulfate); the rest are consistent with Example 3.
[0096] Comparative Example 4
[0097] The difference between this comparative example and Example 2 is that the regenerated micropowder is replaced by an equal amount of uncarbonized ground construction waste powder (the carbonization step is omitted, and the particle size of the ground construction waste powder is the same as that of the regenerated micropowder in Example 2), and the dosage is consistent with Example 2 (that is, the alkali-activated cementitious material of this comparative example includes the following components in parts by weight: 270 parts of slag, 90 parts of fly ash, 18 parts of carbide slag, 90 parts of construction waste micropowder, 45 parts of sodium silicate, 135 parts of organic monomer, 0.15 parts of N,N-methylenebisacrylamide and 2.7 parts of ammonium persulfate); the rest are consistent with Example 2.
[0098] Comparative Example 5
[0099] The difference between this comparative example and Example 2 is that the amounts of carbide slag and sodium silicate are replaced by 0 parts and 63 parts respectively (i.e., the alkali-activated cementitious material of this comparative example includes the following components in parts by weight: 270 parts of slag, 90 parts of fly ash, 0 parts of carbide slag, 90 parts of regenerated micropowder, 63 parts of sodium silicate, 135 parts of organic monomer, 0.15 parts of N,N-methylenebisacrylamide and 2.7 parts of ammonium persulfate); the rest are consistent with Example 2.
[0100] Comparative Example 6
[0101] The difference between this comparative example and Example 2 is that the carbonization temperature of the regenerated micro powder is 60° C., and the rest is consistent with Example 2.
[0102] Comparative Example 7
[0103] The difference between this comparative example and Example 2 is that the carbonization time of the regenerated micro powder is 10 minutes, and the rest is consistent with Example 2.
[0104] Comparative Example 8
[0105] The difference between this comparative example and Example 2 is that the regenerated micro powder is omitted, and the rest is consistent with Example 2.
[0106] Comparative Example 9
[0107] The difference between this comparative example and Example 1 is that the organic monomer is acrylic acid, and the rest is consistent with Example 1.
[0108] Comparative Example 10
[0109] The difference between this comparative example and Example 1 is that the organic monomer is sodium acrylate, and the rest is consistent with Example 1.
[0110] Comparative Example 11
[0111] The difference between this comparative example and Example 3 is that the amount of organic monomer acrylamide is 315 parts, the amount of cross-linking agent is 0.3 parts, and the amount of initiator is 6.3 parts; the rest is consistent with Example 3.
[0112] Experimental example
[0113] The mechanical properties of the all-solid waste alkali-activated cementitious materials of the above-mentioned embodiments and the cementitious materials of the comparative examples were tested respectively. The uniformly mixed materials were injected into 40mm×40mm×40mm and 40mm×40mm×160mm molds, the surfaces were scraped flat, and they were wrapped with plastic wrap and placed in a curing room with a temperature of (20±2)°C and a relative humidity greater than 96%. After curing for a certain period of time, they were demoulded and tested with a universal testing machine at a specified age. The toughness index was calculated according to the standard ASTM C1018 for the area ratio under the peak of the stress-strain compression curve. The specific results are shown in Table 3 below:
[0114] Table 3 Performance test results of all-solid waste alkali-activated materials
[0115]
[0116] Analysis of the above data shows that no acrylamide was added to Comparative Example 1, and there were only inorganic solid waste materials in the system without flexible carbon chains. Therefore, the strength performance was lower than that of other groups, and the toughness index was lower.
[0117] Compared with Comparative Example 2, the strength of Examples 3 to 6 is greatly improved. This is because polyacrylamide is added in Comparative Example 2. Polyacrylamide is a high molecular polymer. When dispersed in water, it mainly plays a role in thickening and making the slurry more stable. It mainly acts by adsorption and wrapping with the gelling material. Therefore, it will not significantly improve the compressive strength, but will reduce the mechanical properties, and will not improve the toughness index.
[0118] Compared with comparative example 3, the strength of Examples 1 to 3 shows a trend of increasing significantly first and then slowly increasing as the amount of recycled micropowder from construction waste increases (when the total amount of fly ash, slag and recycled micropowder remains unchanged). When the amount of recycled micropowder replacing exceeds 40% (the amount of recycled micropowder in comparative example 3 is about 44% of the total amount of fly ash, slag and recycled micropowder, exceeding 40%), the material strength decreases, mainly because after a large amount of recycled micropowder replaces slag, Ca in the system 2+ The content decreases, resulting in a decrease in the production of calcium-containing hydration products - CSH gel; on the other hand, the size of CaCO3 particles is mostly nanometers. When the dosage is large, the unhydrated inorganic materials are wrapped by the CaCO3 particles, preventing hydration, thereby affecting the strength.
[0119] Compared with comparative example 4, the mechanical properties of example 2 are better. This is mainly because the strength of the uncarbonized construction waste recycled micro-powder is mainly provided by the secondary hydration of inorganic components, and a small amount of calcium carbonate participates in the carbonization. The calcium carbonate content increases, and the ultrafine calcium carbonate particles fill the pores, making the structure denser and thus improving the strength.
[0120] In Comparative Example 5, 4% of carbide slag (the amount of carbide slag is 4% of the total amount of fly ash, slag and regenerated micropowder) is replaced with 4% of alkali activator, that is, Comparative Example 5 contains 14% of sodium silicate (4% of carbide slag and 10% of sodium silicate in Example 2); It can be seen from the two sets of data that the compressive strength and toughness index are equivalent, because when the sodium silicate content is high, OH - 、[SiO4] 4- The concentration increases, promoting the active decomposition of slag, fly ash and regenerated micro powder, accelerating hydration, and promoting the formation of CSH, CAH, and CASH gels; after the calcium carbide slag replaces part of the sodium silicate in Example 2, the OH in the calcium carbide slag - , Ca 2+ Fills the reduced OH in the base activator - With [SiO4] 4- , Ca 2+ The increase in hydration promotes the formation of hydration products, so it is feasible to use part of the carbide slag as an alkali activator to reduce the amount of sodium silicate used and improve the solid waste recycling rate; in addition, the 28d flexural strength of Example 2 is even significantly better than that of Comparative Example 5.
[0121] By comparing Comparative Example 6 (the temperature during the carbonization of the recycled micropowder from construction waste is 60°C) and Comparative Example 7 (the carbonization time of the recycled micropowder from construction waste is 10 minutes) with Example 2 (the temperature during the carbonization of the recycled micropowder from construction waste is 100°C and the carbonization time is 1 hour), it can be seen that: whether it is the flexural strength or the compressive strength, Comparative Examples 6 and 7 are far inferior to Comparative Example 2. This is mainly because the carbonization temperature and carbonization time have a greater influence on the reaction of the mineral components in the recycled micropowder with CO2, which in turn causes the composition of the recycled micropowder prepared in Comparative Examples 6 and 7 to change, and thus cannot play a role equivalent to that of the recycled micropowder in Example 2, thereby affecting the mechanical properties.
[0122] Compared with Comparative Example 8, Example 2 has better performance. This shows that the regenerated micropowder in the present invention can improve the performance of the gelling material (especially the flexural strength). Compared with Comparative Examples 9 and 10, Example 1 has better performance. This may be because acrylic acid is weakly acidic and the gelling material system is alkaline, which affects the polymerization reaction of polyacrylic acid and also reduces the alkalinity of the original system. The hydration product of polyacrylate and gelling material does not form an inorganic-organic interpenetrating network structure, and its compatibility with the gelling material is not as good as acrylamide, so the performance of the composite material is not as good as that of Example 1.
[0123] In Comparative Example 11, due to excessive organic components, the material has been plasticized and the actual strength cannot be measured.
[0124] It can be seen from the above table that the performance of Example 3 and Example 6 is relatively excellent. The main reason is that: the calcium sulphoaluminate hydrate and CSH gel will use the CaCO3 provided by the regenerated micropowder as the crystal nucleus, adhere to its surface and grow, promote the hydration reaction, and the negative charge generated by the silanol groups on the binding boundary of the silicate tetrahedron in the CSH gel and the Ca in the CaCO3 2+ Phase equilibrium; CaCO3 reacts with calcium aluminate to generate needle-shaped calcium sulphoaluminate hydrate, calcium carbon aluminate hydrate and semi-carbon calcium carbon aluminate hydrate; CaCO3 usually has a smaller particle size and is dispersed in the liquid phase. It can fill the pores and replace the filling water in the pores to enhance the compactness of the microstructure; acrylamide undergoes polymerization under the action of initiator and crosslinker to generate PAM with a network structure ( Figure 1 (Figure 2 is a schematic diagram of the PAM structure). PAM and the hydration products of the cementitious material are intertwined to form a network structure in which the inorganic skeleton and the flexible carbon chain interpenetrate each other. At the same time, the filling effect of nano-CaCO3 also contributes to the mechanical properties.
[0125] Figure 2The scanning electron microscope image and energy spectrum diagram of Example 3 are obtained by immersing the 28d sample of Example 3 in anhydrous ethanol to terminate hydration for 24h and drying it, and then observing its microscopic morphology after gold spraying (energy spectrum and scanning electron microscope test are carried out simultaneously). It can be seen from the figure that the morphological characteristics of the hydration product are no longer obvious and are wrapped by PAM, but the energy spectrum diagram shows that there are still hydration products such as hydrated calcium silicate gel. It is also because of such a dense structure that the toughness and strength of the all-solid waste cementitious material are significantly improved.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A fully solid waste alkali-activated gelling material, characterized in that: The all-solid waste alkali-activated cementitious material comprises the following components in parts by weight: 60-140 parts of fly ash, 200-360 parts of slag, 5-45 parts of carbide slag, 45-180 parts of recycled micro powder, 30-70 parts of alkali activator, 45-225 parts of organic monomer and 120-260 parts of water; Also included are crosslinkers and initiators.
2. The all-solid waste alkali-activated gelling material according to claim 1, characterized in that: The organic monomer is acrylamide, the cross-linking agent is N-(hydroxymethyl)acrylamide and / or N,N-methylenebisacrylamide, and the initiator is ammonium persulfate and / or potassium persulfate; In parts by weight, the amount of the crosslinking agent is 0.04-2 parts, and the amount of the initiator is 0.09-5 parts.
3. The all-solid waste alkali-activated gelling material according to claim 2, characterized in that: The all-solid waste alkali-activated cementitious material includes the following components in parts by weight: 68-101 parts of fly ash, 200-305 parts of slag, 18 parts of carbide slag, 45-180 parts of recycled micropowder, 45 parts of alkali activator, 90-225 parts of organic monomer, 0.1-1.08 parts of cross-linking agent, 1.8-4.5 parts of initiator and 225 parts of water.
4. The all-solid waste alkali-activated gelling material according to claim 1, characterized in that: The regenerated micropowder is prepared by a method comprising the following steps: (1) Putting construction waste into a crusher and crushing it into a particle size of 20-30 mm to obtain construction waste particles; (2) introducing a gas containing carbon dioxide into the construction waste particles obtained in step (1) to carbonize them, thereby obtaining carbonized particles; (3) Grinding the carbonized particles obtained in step (2) to micrometer level to obtain the regenerated micro powder.
5. The all-solid waste alkali-activated gelling material according to claim 4, characterized in that: In step (2), the carbonization temperature is 80-100° C., the carbonization pressure is 0.15-0.25 MPa, and the carbonization time is 0.5-1 h.
6. The all-solid waste alkali-activated gelling material according to claim 1, characterized in that: 90% of the particle size of the regenerated micro powder is within the range of 0.1-25 μm; 90% of the particle sizes of all components of the all-solid waste alkali-activated cementitious material are below 35.3 μm.
7. The method for preparing the all-solid waste alkali-activated gelling material according to any one of claims 1 to 6, characterized in that: The steps include: Step S1, drying fly ash, slag and carbide slag respectively; Step S2, weighing fly ash, slag, carbide slag, recycled micropowder, organic monomer, crosslinking agent and initiator according to the formula amount, and adding them into a stirring device in sequence for stirring and mixing until they are uniformly mixed; Step S3, weighing water and alkaline activator according to the formula amount, adding them into a blender, and stirring to obtain a uniformly mixed activator solution; Step S4, putting the raw materials mixed evenly in step S2 into the activator solution obtained in step S3, stirring at a first stirring rate for a first time, and then stirring at a second stirring rate for a second time, to obtain the all-solid waste alkali-activated gelling material.
8. The method for preparing the all-solid waste alkali-activated gelling material according to claim 7, characterized in that: In step S4, the first stirring rate is 30-60 r / min, and the first time is 2-5 min; The second stirring rate is 90-110 r / min, and the first time is 2-5 min.
9. The method for preparing the all-solid waste alkali-activated gelling material according to claim 7, characterized in that: In step S1, the drying temperature is 50-80°C and the drying time is 2.5-3.5h; In step S2, the stirring rate is 55-65 r / min and the stirring time is 2-5 min; In step S3, the stirring rate is 55-65 r / min, and the stirring time is 1-3 min.
Citation Information
Cited By
High-performance sprayed concrete for subsea tunnel and construction application method of high-performance sprayed concrete
CN120903911A